BLOCKCHAIN TRANSPARENCY AS A DIGITAL GOVERNANCE MECHANISM: EVIDENCE FROM PRICE TRANSMISSION AND VALUE DISTRIBUTION IN AGRIBUSINESS SUPPLY CHAINS - Riswandi, D Iwan (LPPM Universitas Jambi, 2026)
Price transmission asymmetry and unequal value capture remain persistent inefficiencies in smallholder-based agro-processing chains. This study investigates whether blockchain-enabled transparency functions as digital governance that improves price adjustment efficiency and promotes fairer value distribution in agricultural supply chains. An integrated Error Correction Model (ECM) and Vector Error Correction Model (VECM) framework is applied to estimate short-run and long-run price dynamics between farm-gate cassava prices and downstream processing prices. A Blockchain Transparency Index (BTI), capturing transaction coverage, timeliness, and contractual automation, is constructed and incorporated as an interaction term to test its moderating role, while farmer price share ratios and value dispersion indices assess distributional outcomes. The results confirm cointegration and asymmetric price transmission along the chain; higher blockchain transparency significantly accelerates adjustment toward long-run equilibrium, reduces transmission asymmetry, increases farmer price shares, and lowers value dispersion. Drawing on Resource-Based View and Institutional Economics, the findings demonstrate that blockchain transparency operates as a strategic digital capability and governance mechanism that reduces information asymmetry and transaction costs. By embedding a measurable digital governance index within dynamic price transmission modeling, this study provides novel empirical evidence linking technological transparency to distributional and welfare-related outcomes. The results imply that cooperative-led blockchain governance offers a scalable pathway for aligning efficiency and equity in emerging agri-food systems.